The tax compliance costs of large corporate taxpayers in Indonesia - Susila, Budi; Pope, Jeffrey (Taxation Institute of Australia, 2012)
This article reports the results of the first research on the compliance costs of large corporate taxpayers in Indonesia in 2010. Using a mail survey of 3,000 questionnaires with a response rate of 8.2%, the main finding is that the gross costs of compliance for large taxpayers are significant, estimated to be IDR 12.3 trillion, and account for3.16% of tax revenue for large corporations and 0.19% of the Gross Domestic Product in 2010. Overall average costs per large company are IDR420,933,442 (aroundA$55,000 at the December 2010 exchange rate). Average costs differ markedly across the various economic sectors. The majority of the costs are incurred on human resources in the companies (staff, managers, directors). The research shows that costs are regressive in terms of the number of employees, the amount of total assets, the annual turnover, and the tax payments. The components of compliance costs are broken down into: routine and non-routine costs 86% and 14%, internal and external costs 73% and 27%, computational costs and planning costs 73% and27%, respectively. Cash flow benefits and tax deductibility benefits, both being offsets of gross costs, represent 24% and 25% of gross compliance costs respectively. The article concludes by succinctly setting this timely research in an international context, identifying its limitations and discussing the study’s significance for Indonesian tax policy, with a recommendation for further work in the tax compliance costs field.